2019
DOI: 10.3390/antiox8100424
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Selected Antioxidants on Naproxen Photodegradation in Aqueous Media

Abstract: A photostabilization strategy is an important aspect of quality assurance for photosensitive compounds. This study focused on the photoprotective effects of selected antioxidants including the effect of L-ascorbic acid (AA) on naproxen (NX) photodegradation in aqueous media. NX degradation during ultraviolet light (UV) irradiation and the protective effects of selected antioxidants were monitored by high-performance liquid chromatography (HPLC). The addition of AA induced the suppression of NX photodegradation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…It is reported that NX is photo-converted to its photoproducts, via the generation of radical species, followed by oxidation [ 12 , 13 ]. Some antioxidants, including ascorbic acid and polyphenols, suppressed NX photodegradation due to their antioxidative potencies [ 8 ]. Other studies also showed protective effects of the antioxidative agents on the photosensitive compounds [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is reported that NX is photo-converted to its photoproducts, via the generation of radical species, followed by oxidation [ 12 , 13 ]. Some antioxidants, including ascorbic acid and polyphenols, suppressed NX photodegradation due to their antioxidative potencies [ 8 ]. Other studies also showed protective effects of the antioxidative agents on the photosensitive compounds [ 14 , 15 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results showed that the UV filtering ability is a major determinant for the photoprotective effect on NX photodegradation, compared to the antioxidative potency. Our previous reports indicated that polyphenol compounds such as quercetin and catechin showed more photostability effects on NX photodegradation, compared to ascorbic acid, on account of having more antioxidative effects [ 8 ]. It is possible that they might be a good photostabilizer as they have a polyphenol backbone, which is well-known as a UV filter.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our previous study, naproxen and L-ascorbic acid (AA) in a solution were irradiated by a black light lamp for 1 hr. The residual amount of naproxen was 95.82% while that of AA was 34.99% [11]. These reports suggest that AA is more photosensitive than naproxen, and its analysis through a PDA detector might be interrupted due to light emission especially at shorter wavelength.…”
Section: Introductionmentioning
confidence: 87%